Antibiotic stewardship bundle for uncomplicated gram-negative bacteremia at an academic health system: a quasi-experimental study - Juliana DiPietro; Yanina Dubrovskaya; Kassandra Marsh; Arnold Decano; John Papadopoulos; Dana Mazo; Kenneth Inglima; Vincent Major; Jonathon So; Samuel Yuditskiy; Justin Siegfried (Cambridge University Press, 2024)
Abstract Objective: To evaluate whether an antimicrobial stewardship bundle (ASB) can safely empower frontline providers in the treatment of gram-negative bloodstream infections (GN-BSI). Intervention and Method: From March 2021 to February 2022, we implemented an ASB intervention for GN-BSI in the electronic medical record (EMR) to guide clinicians at the point of care to optimize their own antibiotic decision-making. We conducted a before-and-after quasi-experimental pre-bundle (preBG) and post-bundle (postBG) study evaluating a composite of in-hospital mortality, infection-related readmission, GN-BSI recurrence, and bundle-related outcomes. Setting: New York University Langone Health (NYULH), Tisch/Kimmel (T/K) and Brooklyn (BK) campuses, in New York City, New York. Patients: Out of 1097 patients screened, the study included 225 adults aged ≥18 years (101 preBG vs 124 postBG) admitted with at least one positive blood culture with a monomicrobial gram-negative organism. Results: There was no difference in the primary composite outcome (12.9% preBG vs. 7.3% postBG; P = 0.159) nor its individual components of in-hospital mortality, 30-day infection-related readmission, and GN-BSI recurrence. Vancomycin (VAN) discontinuation (DC) was done more frequently by the primary team in postBG (37.9% vs 66.7%; P < 0.001). In postBG, de-escalation done by the primary team increased by 8.8%, P = 0.310 and there was an 11.1% increase in the use of aminopenicillin-based antibiotics, P = 0.043. Conclusions: GN-BSI bundle worked as a nudge-based strategy to guide providers in VAN DC and increased de-escalation to aminopenicillin-based antibiotics without negatively impacting patient outcomes.